28.9k views
2 votes
Solve the equation

{5}^(n + 1) - {5}^(n) + {5}^(n - 1) = 105


User Alchi
by
5.0k points

2 Answers

1 vote
n=2 is the correct answer yes
User NGoline
by
5.6k points
3 votes

Answer:

n=2

Explanation:

Hello, please consider the following.


{5}^(n + 1) - {5}^(n) + {5}^(n - 1) = 105\\\\5^(n-1)(5^2-5+1)=5^(n-1)(25-5+1)=21*5^(n-1)=105\\\\5^(n-1)=(105)/(21)=5=5^1\\\\\text{It means that}\\\\n-1=1 <=> n=2

Let me know if you need more details.

Thank you

User Shurmajee
by
5.3k points